The CX3CL1-CX3CR1 chemokine axis can contribute to tumor immune evasion and blockade with a novel CX3CR1 monoclonal antibody enhances response to anti-PD-1 immunotherapy - Chaudhri, Apoorvi; Bu, Xia; Wang, Yunfei; Gomez, Michael; Torchia, James A.; Hua, Ping; Hung, Shao-Hsi; Davies, Michael A.; Lizee, Gregory A.; Andrian, Ulrich von; Hwu, Patrick; Freeman, Gordon J. (Frontiers in Immunology, 2023)
CX3CL1 secreted in the tumor microenvironment serves as a chemoattractant playing a critical role in metastasis of CX3CR1 expressing cancer cells. CX3CR1 can be expressed in both cancer and immune-inhibitory myeloid cells to facilitate their migration. We generated a novel monoclonal antibody against mouse CX3CR1 that binds to CX3CR1, blocks the CX3CL1-CX3CR1 interaction and antagonizes the pro-tumorigenic outcome of this axis. This monoclonal antibody reduces migration of tumor cells and decreases secretion of immune suppressive soluble mediators from the tumor. In combination with anti-PD-1 immunotherapy, this CX3CR1 monoclonal antibody enhances survival in an immunocompetent mouse colon carcinoma model through a decrease in tumor-promoting myeloid populations. We further explore the immune evasion strategies implemented by this axis and find that it initiates a resistance program in cancer cells that results in 1) facilitation of tumor cell migration, 2) secretion of soluble mediators to generate a pro-metastatic niche, 3) secretion of soluble mediators to attract myeloid populations, and 4) generation of tumor-inflammasome. Thus, this axis is involved in the mechanisms of resistance to anti-PD-1 immunotherapy and the combination therapy can overcome a portion of the resistance mechanisms to anti-PD-1.